Black hole masses from X-rays - Zhou, X.; Soria, Roberto (2012)
We discuss two methods to estimate black hole (BH) masses using X-ray data only: from the X-ray variability amplitude and from the photon index G. The first method is based on the anti-correlation between BH mass and X-ray variability amplitude. Using a sample of AGN with BH masses from reverberation mapping, we show that this method shows small intrinsic scatter. The second method is based on the correlation between G and both the Eddington ratio L bol/L Edd and the bolometric correction L bol/L 2-10keV. © International Astronomical Union 2013.